High Prevalence of Cardiometabolic Comorbidities Among Children and Adolescents With Severe Obesity From a Large Metropolitan Centre (Hangzhou, China) - Wang, Jinling; Lin, Hu; Chiavaroli, Valentina; Jin, Binghan; Yuan, Jinna; Huang, Ke; Wu, Wei; Dong, Guanping; Derraik, José G. B.; Fu, Junfen (Frontiers in Endocrinology, 2022)
Objective This study aimed to describe the clinical characteristics of children and adolescents with obesity, and the prevalence of cardiometabolic comorbidities over 10 years in this population from a large metropolitan centre in China. Methods This was a cross-sectional study (2008–2017) of patients aged <18 years with obesity [body mass index (BMI) ≥ 95th percentile for age and sex] enrolled at the Department of Endocrinology, Children’s Hospital of Zhejiang University School of Medicine (Hangzhou, Zhejiang Province). Clinical assessments included anthropometry, blood pressure, liver ultrasound, lipid profile, oral glucose tolerance test, and uric acid. For examination of outcomes, our study cohort was stratified by sex and age bands (<10 vs. ≥10 years), with the study period also split into two strata (2008–2012 and 2013–2017). Results A total of 2,916 patients (1,954 boys and 962 girls) were assessed at a mean age of 10.5 years. Patients almost invariably presented severe obesity (median BMI SDS = 2.98; Q1 = 2.60, Q3 = 3.39). Obesity-related comorbidities were common among boys and girls, including type 2 diabetes mellitus (2.6% and 3.6%, respectively), abnormal glycaemia (33.6% and 35.5%, respectively), hypertension (33.9% and 32.0%, respectively), dyslipidaemia (35.2% and 39.6%, respectively), hyperuricaemia (16.2% and 8.3%, respectively), acanthosis nigricans (71.9% and 64.0%, respectively), abnormal liver function (66.9% and 47.0%, respectively), and non-alcoholic fatty liver disease (NAFLD) (63.8% and 45.1%, respectively); 38.7% of boys and 44.4% of girls aged ≥10 years had metabolic syndrome. Notably, the incidence of many cardiometabolic comorbidities was in 2013–2017 compared to 2008–2012. For example, rates of hypertension among boys aged <10 years and aged ≥10 years rose from 28.4% and 26.5% to 48.0% and 35.8%, respectively, and in girls from 20.3% and 20.8% to 41.7% and 39.6%, respectively. In 2013–2017, 9.5% of girls in the older group had metabolic syndrome compared to 2.2% in 2008–2013. Conclusions We observed a high incidence of obesity-related cardiometabolic comorbidities among Chinese children and adolescents with severe obesity over 10 years. It was particularly concerning that rates of several comorbidities rose markedly over the study period, highlighting the need to address the obesity epidemic early in life (in China and elsewhere) to prevent the development of obesity-related comorbidities and, subsequently, of overt disease.